Clinical examination of the knee: know your tools for diagnosis of knee injuries - Rossi Roberto; Dettoni Federico; Bruzzone Matteo; Cottino Umberto; D'Elicio Davide G; Bonasia Davide E (BMC, 2011)
Abstract The clinical evaluation of the knee is a fundamental tool to correctly address diagnosis and treatment, and should never be replaced by the findings retrieved by the imaging studies carried on the patient. Every surgeon has his own series of exams with whom he is more confident and on whom he relies on for diagnosis. Usually, three sets of series are used: one for patello-femoral/extensor mechanism pathologies; one for meniscal and chondral (articular) lesions; and one for instability evaluation. This review analyses the most commonly used tests and signs for knee examination, outlining the correct way to perform the test, the correct interpretation of a positive test and the best management for evaluating an injured knee both in the acute and delayed timing.